Obesity and related factors among Jordanian women of reproductive age based on three DHS surveys, 2002-2012 - Al-Nsour, Mohannad; Arbaji, Ali (DHS Working Papers No. 115, 2014)
Objectives: The main objective of this study is to analyze the trends in obesity among Jordanian women of reproductive age over the 10-year period from 2002 to 2012 based on three Demographic and Health Surveys (DHS). Furthermore, the study aims to analyze the possible factors predicting obesity among Jordanian women.